Telipogon cruentilabrum (Orchidaceae: Oncidiinae): a new species from mid-western Ecuador, long misidentified as T. dendriticus - Iturralde, Gabriel A.; Jiménez, Marco M.; Monteros, Marco F.; Martel, Carlos; Baquero, Luis E. (Phytotaxa, 2025)
Telipogon cruentilabrum, from the cloud montane forest of mid-western Ecuador, is proposed as a new species. Plants of T. cruentilabrum are characterized by the yellow flowers with dark yellow longitudinal veins and tortuous, occasionally branched transversal lines; petals and lip with heavily undulate blades and irregularly reflexed margins; petals with a dark red-brown, swollen base; lip with a conspicuous radial, red-purple basal stain; a large, dark purple-red, elevated callus; anther profusely surrounded by three tufts of red-purple setae; and the stigma wide, sub-trapezoid, dark purple. This species has long been misidentified as T. dendriticus. Although in the holotype no callus is observed on the lip, and in its description and subsequent citations a callus is never mentioned. We provide here a detailed description, figures, distributional map and comparison with its morphological most similar species, T. tamboensis, and also include arguments to discriminate it from T. dendriticus.